Could COVID‐19 Infect the Consumer Prices Index?. (6th July 2020) - Blundell, Richard; Griffith, Rachel; Levell, Peter; O'Connell, Martin
Abstract: The spread of COVID‐19 has led to sweeping changes in the way households work, spend their time and shop, resulting in different shopping patterns and rapid price changes in some goods. How will changes such as these be reflected in headline inflation measures such as the Consumer Prices Index (CPI)? This paper discusses problems in interpreting the CPI as a measure of how the cost of living is changing during the lockdown.